An Evaluation of the PUSPAGA SAMARADA Program in Improving the Quality of Child Parenting in Sukabumi City - Zahra Aprilita Herdani; Yana Fajar FY Basori; Andi Mulyadi (International Journal of Social Sciences and Humanities, 2026)
This study aims to evaluate the Pusat Pembelajaran Keluarga (PUSPAGA) Sakinah, Mawaddah, Rahmah, dan Dakwah (SAMARADA) Program in improving the quality of child parenting in Sukabumi City. This research employed a qualitative method with a descriptive approach. Data were collected through interviews, observation, and documentation. The informants consisted of representatives from DP2KBP3A Sukabumi City, the coordinator of PUSPAGA SAMARADA, a psychologist, and community beneficiaries. The evaluation model used in this study was the CIPP model, which includes context, input, process, and product. The findings indicate that the PUSPAGA SAMARADA Program has been implemented fairly well and is relevant to community needs, particularly in providing consultation, counseling, education, and referral services related to child parenting and family issues. The program provides benefits for the community by improving understanding of parenting patterns, family communication, and the handling of parenting problems. However, the implementation of the program still faces several obstacles, including limited human resources, budget, facilities, and uneven public dissemination. This study contributes to the literature on family support services by providing a comprehensive evaluation of the PUSPAGA SAMARADA Program using the CIPP model, highlighting both its achievements and implementation challenges in improving parenting practices at the local level. Therefore, institutional support, public outreach, and service development need to be strengthened so that the PUSPAGA SAMARADA Program can operate more optimally in improving the quality of child parenting in Sukabumi City.